Pengaruh IkhtilÃ¢f al-á¸¤adÃ®th terhadap Penalaran Hukum Islam - Masruhan Masruhan (Islamica: Jurnal Studi Keislaman, 2013)
Difference of opinion is highly respected in Islam. The Prophet of Islam is even reported to have said that, difference of opinion is divine providence?. This paper tackles this issue particularly within the science of prophetic tradition, and relates it to the way Muslim legalists develop the logics of law. The paper first argues that difference of opinion is not only natural but also needed in legal and social life. It is also viewed in terms of social conflict a requirement for a social integration. The paper speaks of the two sources of Islam?the Quran and the prophetic tradition?as supportive of this difference of opinion and shows that the prophet, his companions, and closest followers are all involved in debate stemmed from their difference of opinion. This difference is the natural consequence of the difference in the level of understanding, different language, culture, way of thinking, custom, and the extent to which the companions are in engaged in the activities of the prophet.